Impact of Agriculture Products and Market Development Build up Nepalese Economy - Pandey, Ananyaa; Mahat, Kushendra Bahadur; Dhungel, Lila Nath (A Peer Reviewed Journal on Social Sciences, 2024)
Agriculture has long been the backbone of Nepal’s economy, providing livelihoods for a significant portion of the population, particularly in rural areas. Agricultural products, especially staple crops like maize, paddy, wheat, and other food staples, play a central role in Nepal’s socio-economic development. Strengthening agricultural markets is not only crucial for improving food security but also for fostering economic growth, reducing poverty, and promoting self-sufficiency. This Research examines the role of agricultural products and market strengthening in contributing to Nepal’s economic growth. Research efforts on the part of Agriculture commodity marketplaces promoting productive financial growth of Nepal, specifically examining main market place in Bagmati Province, including Banepa, Narayanghat, and Nuwakot. The findings highlight maize, paddy, and wheat as the main commodities grown in the region, which are in high demand due to their daily consumption and staple nature. The study also notes that the Terai region and Indian supply channels are critical to the local economy, with much of the supply coming from these areas. A key finding of the study is that approximately 60% of local agricultural production is available for only 2-3 months, indicating a potential gap in year-round self-sufficiency. To address this issue, the study recommends enhancing the promotion and management of local production, which would not only reduce dependency on external supply chains but also improve the overall economic stability of the region. Promoting self-sufficiency through better agricultural practices, infrastructure improvements, and effective policy interventions could help balance the supply-demand disparity, ensuring more consistent availability of key commodities.